ШВИДКОДІЮЧИЙ АДАПТИВНИЙ ЗАХИСТ ВІД КОРОТКИХ ЗАМИКАНЬ В ЕЛЕКТРИЧНИХ МЕРЕЖАХ MICROGRID З РОЗПОДІЛЕНОЮ ГЕНЕРАЦІЄЮ - Гребченко, М.В.; Єрьоменко, Є.В. (Інститут електродинаміки НАН України, Київ, 2021)
Protection against short circuits in microgrid networks with distributed generation is proposed, in which the power of the power sources and loads are constantly changing, which leads to a change in the sensitivity of relay protection. The response current of the proposed protection automatically adapts to the current value of the line operating current. The protection includes measures to block its action in the event of short-term interference in current circuits. Protection is installed on both sides of the line and protects the entire line, provides a stable mode of operation of the network due to the quick shutdown of short circuits. The algorithm of operation and the scheme for implementing protection are given. The protection operation was tested using the parameters of the real short circuit mode. References 7, figures 3.